The evolutionary and ecological significance of phylloclade formation : A morpho-anatomical approach - Dörken, Veit; Ladd, Philip G.; Parsons, Robert F. (My University, 2024)
Instead of leaves, in a few species the main photosynthetic organ is a flattened structure that can be a modified branch (e.g. Ruscus, Jacksonia) or a fused combination of branch and leaf tissue (e.g. Phyllocladus) called a phylloclade. The phylloclades of Phyllocladus lack xeromorphic features in their wet habitat. They are broad under the low light conditions as are those of Ruscus which can occur in forest understories. However Ruscus is also common in dry habitats and shows numerous xeromorphic features. In Jacksonia extensive sclerenchyma and thick cuticle protect the phylloclades from desiccation damage in xeric seasonal conditions. Despite former contrary definitions of phylloclades we advocate they be defined as pseudo-petiolate organs determinate in growth which arise from axillary buds in the axil of reduced leaves and resemble a leaf.
Keywords: Leaf reduction; Drought; Shade; Photosynthesis; Light harvesting; Environment; Climate change; 570